2007
DOI: 10.1177/0959683607076448
|View full text |Cite
|
Sign up to set email alerts
|

Age and significance of aeolian sediment reworking on high plateaux in the Scottish Highlands

Abstract: Holocene aeolian sand sheets at the margins of high-level deflation surfaces in the Scottish Highlands commonly comprise two units: a lower weathered unit representing slow accumulation throughout much or all of the Holocene, and an upper unit of structureless sand that is inferred to represent recent erosion of aeolian deposits and aeolisols from adjacent plateaux. OSL dating of samples from above and below the upper-lower unit contact at three sites in NW Scotland places the onset of upper unit sediment accu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(10 citation statements)
references
References 33 publications
(44 reference statements)
0
9
0
Order By: Relevance
“…Continuous power or continuous wave OSL (CW-OSL) was conducted in all measurements. Similar to other recent studies (Lukas et al, 2007;Morrocco et al, 2007;Spencer and Robinson, 2008;Ashley et al, 2011;Rittase et al, 2014), post-infrared optically stimulated luminescence (post-IR OSL) was used to measure the luminescence from the quartz grains. This procedure removes charge sensitive to infrared stimulation, commonly associated with remnant feldspathic minerals, before measuring OSL from the quartz grains.…”
Section: Equivalent Dose Estimationmentioning
confidence: 99%
“…Continuous power or continuous wave OSL (CW-OSL) was conducted in all measurements. Similar to other recent studies (Lukas et al, 2007;Morrocco et al, 2007;Spencer and Robinson, 2008;Ashley et al, 2011;Rittase et al, 2014), post-infrared optically stimulated luminescence (post-IR OSL) was used to measure the luminescence from the quartz grains. This procedure removes charge sensitive to infrared stimulation, commonly associated with remnant feldspathic minerals, before measuring OSL from the quartz grains.…”
Section: Equivalent Dose Estimationmentioning
confidence: 99%
“…The subsequent deposition of an upper unit of fresh unweathered sand up to 2.3 m thick on top of the older weathered deposits on lee slopes indicates catastrophic erosion and concomitant redeposition of plateau-surface sands and aeolisols. Opticallystimulated luminescence (OSL) dating of the boundary between the lower weathered sand unit and the upper unit of fresh sand on An Teallach demonstrates that widespread erosion of stable vegetated sand deposits on the plateau commenced within the interval AD 1550-1700 (Morrocco et al, 2007). Though the trigger of widespread erosion of plateau deposits cannot be conclusively established, it is notable that this interval coincides with a period of marked climatic deterioration characterized by prolonged snow-lie on high ground and an increase in the frequency and ferocity of cyclonic storms (Lamb, 1977(Lamb, , 1979Mitchell, 1999).…”
Section: Wind Action On Mountainsmentioning
confidence: 99%
“…Interestingly, OSL dating of lee-slope accumulations of windblown sediments on the Red Cuillin on Skye and Fionn Bheinn near Achnasheen showed that widespread wind erosion of plateau soils commenced at these sites at roughly the same time, implying that this was a widespread phenomenon in NW Scotland. At a site in the Central Grampians, however, deflation and redeposition of plateausurface soils apparently did not commence until about AD 1900 (Morrocco et al, 2007). Probably the most fascinating upland sand sheet is that on The Storr (719 m), the highest point of the Trotternish escarpment in northern Skye.…”
Section: Wind Action On Mountainsmentioning
confidence: 99%
“…Continuous power or continuous wave OSL (CW-OSL) was conducted in all measurements. Similar to other recent studies, post-infrared optically stimulated luminescence (post-IR OSL) was used to measure the luminescence from the quartz grains (Lukas et al, 2007;Morrocco et al, 2007;Spencer & Robinson, 2008). This procedure removes charge sensitive to infrared stimulation, commonly associated with remnant feldspatic minerals, before measuring OSL from the quartz grains.…”
Section: Equivalent Dose (D E ) Measurement Proceduresmentioning
confidence: 98%